2021
DOI: 10.1002/ecy.3541
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of lightning to biomass turnover, gap formation and plant mortality in a tropical forest

Abstract: Lightning is a common source of disturbance, but its ecological effects in tropical forests are largely undescribed. Here we quantify the contributions of lightning strikes to forest turnover and plant mortality in a lowland Panamanian forest using a real‐time lightning monitoring system. We examined 2,195 lightning‐damaged trees distributed among 93 different strikes. None exhibited scars or fires. On average, each strike disturbed 451 m2 (95% CI: 365–545 m2), created a canopy gap of 304 m2 (95% CI 198–454 m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The size distribution of canopy gaps will vary along environmental gradients, since forest dynamics is controlled by environmental variables (Phillips et al, 2004;Quesada et al, 2012). Previous studies have found correlations between α and climate variables, topography and soils (Goodbody et al, 2020;Goulamoussène et al, 2017), as well as wind and lightning (Gora et al, 2021). In the Amazon, mortality and turnover rates mainly vary along an east-west gradient coinciding with a soil fertility gradient, with higher tree mortality and turnover rates in the rich soils of western Amazon compared to the eastern Amazon (Aragão et al, 2009;Esquivel-Muelbert et al, 2020;Phillips et al, 2004;Quesada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The size distribution of canopy gaps will vary along environmental gradients, since forest dynamics is controlled by environmental variables (Phillips et al, 2004;Quesada et al, 2012). Previous studies have found correlations between α and climate variables, topography and soils (Goodbody et al, 2020;Goulamoussène et al, 2017), as well as wind and lightning (Gora et al, 2021). In the Amazon, mortality and turnover rates mainly vary along an east-west gradient coinciding with a soil fertility gradient, with higher tree mortality and turnover rates in the rich soils of western Amazon compared to the eastern Amazon (Aragão et al, 2009;Esquivel-Muelbert et al, 2020;Phillips et al, 2004;Quesada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In some areas, lightning strikes have become a major local health risk (Uman, 1994 ; Rakov and Uman, 2003 ). In addition, lightning strikes are closely related to forest wildfire, which is one of the main causes of forest ecosystem imbalance and tree death (Clarke et al, 2019 ; Fill et al, 2019 ; Gora et al, 2021 ). Furthermore, an increase in surface pollutants is considered to be closely related to the frequency of lightning (Gharaylou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We located lightning strikes using a combination of cameras and electric field change meters across a progressively increasing study area (from 2.25 km 2 to 15 km 2 ; Yanoviak et al ., 2017; Gora et al ., 2021). We surveyed lightning strikes recorded on multiple cameras from 2015 to 2019.…”
Section: Methodsmentioning
confidence: 99%
“…We quantified lightning disturbance characteristics in association with lianas and with inferred patterns of electric current transfer in a lowland Panamanian forest. Specifically, we combined a unique dataset of systematically located lightning strikes (patterns of plant damage and death among these strikes were previously published in Yanoviak et al ., 2020 and Gora et al ., 2021) with visual observations of plant damage patterns and forest plot data describing co‐located tree and liana communities. We hypothesized that lianas influence the severity and area (spatial extent) of lightning disturbance in forests.…”
Section: Introductionmentioning
confidence: 99%